2017
DOI: 10.3389/fnmol.2017.00246
|View full text |Cite
|
Sign up to set email alerts
|

The Microvascular Gap Junction Channel: A Route to Deliver MicroRNAs for Neurological Disease Treatment

Abstract: Brain microvascular endothelial cells (BMECs) separate the peripheral blood from the brain. These cells, which are surrounded by basal lamina, pericytes and glial cells, are highly interconnected through tight and gap junctions. Their permeability properties restrict the transfer of potentially useful therapeutic agents. In such a hermetic system, the gap junctional exchange of small molecules between cerebral endothelial and non-endothelial cells is crucial for maintaining tissue homeostasis. MicroRNA were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Since carbenoxolone inhibited the transfer of both miRNAs, it is highly likely that they use the same GJIC pathway to accomplish their transfer. Moreover, GJIC between GBM cells and HMECs lose their functionality in vitro after a few days; however, miR-5096 still manages to pass in a less efficient manner, probably through exosome release [69,93,94].…”
Section: Intercellular Communication-enemy Propagandamentioning
confidence: 99%
“…Since carbenoxolone inhibited the transfer of both miRNAs, it is highly likely that they use the same GJIC pathway to accomplish their transfer. Moreover, GJIC between GBM cells and HMECs lose their functionality in vitro after a few days; however, miR-5096 still manages to pass in a less efficient manner, probably through exosome release [69,93,94].…”
Section: Intercellular Communication-enemy Propagandamentioning
confidence: 99%
“…It has been demonstrated that miR-145-5p expressed in HMEC and miR-5096 derived from GBM cells can transfer between the two types of cells through GJIC. MiR-5096 may promote GBM invasiveness and angiogenesis after transferring into HMEC, while miR-145-5p acts as a tumor suppressor after moving into GBM cells (Thuringer et al, 2017 ). Direct cell-to-cell communication via GJIC is superior to indirect communication in terms of specificity and efficiency.…”
Section: Ncrna-related Intercellular Communications That Regulate Glioma Angiogenesismentioning
confidence: 99%
“…As mentioned above, miRNAs are related to the mechanisms of I/R, which has opened new fields of research for not only biomarkers, but also therapeutics of ischemic diseases. And iPSC (inducible pluripotent stem cells) derived BMEC (brain microvascular endothelial cells) have been designed to transfer miRNAs over the years, overcome the difficulty of crossing the blood brain barrier [16] ,locked nucleic acid (LNA) and chemically modified miRNAs vectors overcome the stability of miRNAs in vivo, make it possible for miRNAs based gene therapy to cure I/R. Yet, miRNAs treatment is far from safe and effective clinical application.…”
Section: Prospectmentioning
confidence: 99%